High Intensity Strength Training For Better Body Composition - Westcott, W. L.
We have recently examined the effects of combined high-intensity training techniques on body composition changes in well-conditioned participants. The six-week advanced exercise program included slow training, breakdown training, assisted training, and pre-exhaustion training. The 48 subjects added 2.5 pounds of lean weight and lost 3.3 pounds of fat weight as a result of their training efforts, which represented more improvement than we expected from regular strength exercisers.